Ventricular Repolarisation Indices in Relation with Coronary Artery Lesions - Venclovienė, J.; Bertašienė, Z.; Kaminskienė, S.; Jaruševičius, G.; Blužaitė, I. (Elektronika ir Elektrotechnika, 2009)
The aim of the study was to find rest electrocardiogram (ECG) indices which are valuable do detect patients with coronary artery (CA) lesions in proximal or distal CA segments. The study population consisted of 293 patients with stable angina pectoris. Stenosis of CA lumen ≥50 % was diagnozed in 62 % (181) of patients. The patients were divided into groups: without CA stenosis, proximal stenosis in 1, 2 or 3 CA, distal stenosis in 1,2, 3 CA, and rest ECG indices (minimal, maximal and mean QRS duration, JT and JT apex dispersion, T loop area and T loop index, αQTS-T) were measured. In our study T loop area and T loop index were associated with CA stenosis in distal segments. Ventricular repolarisation indices (JT and JT apex dispersion) and axis angle αQTS-T were associated with CA stenosis when lesions were in proximal CA segments. Ill. 1, bibl. 6 (in English; summaries in English, Russian and Lithuanian).